Sustainable Manufacturing: Challenges, Solutions and Implementation Perspectives - Stark, Rainer; Seliger, Günther; Bonvoisin, Jérémy (Sustainable Production, Life Cycle Engineering and Management, 2017)
Manufacturing, Machines, Tools; Sustainable Development; Energy Efficiency; Production